An empirical comparison of fixed-strength and mixed-strength for interaction coverage based prioritization - Huang, Rubing; Zhang, Quanjun; Chen, Tsong Yueh; Hamlyn-Harris, James; Towey, Dave; Chen, Jinfu (Institute of Electrical and Electronics Engineers, 2018)
Test case prioritization (TCP) plays an important role in identifying, characterizing, diagnosing and correcting faults quickly. TCP has been widely used to order test cases of different types, including model inputs (also called abstract test cases). Model inputs are constructed by modeling the program according to its input parameters, values, and constraints, and has been used in different testing methods, such as combinatorial interaction testing, and software product line testing. Interaction coveragebased test case prioritization (ICTCP) uses interaction coverage information derived from the model input to order inputs. Previous studies have focused generally on the ﬁxed-strength ICTCP, which adopts a ﬁxed strength(i.e.,thelevelofparameterinteractions)tosupporttheICTCPprocess.Itisgenerallyacceptedthat using more strengths for ICTCP, i.e., mixed-strength ICTCP, may give better ordering than ﬁxed-strength. To conﬁrm whether mixed-strength is better than ﬁxed-strength, in this paper we report on an extensive empirical study using ﬁve real-world programs (written in C), each of which has six versions. The results oftheempiricalstudiesshowthatmixed-strengthhasbetterratesofinteractioncoverageoverallthanﬁxedstrength, but they have very similar rates of fault detection. Our results also show that ﬁxed-strength should be used instead of the mixed-strength at the later stage of software testing. Finally, we offer some practical guidelinesfortesterswhenusinginteractioncoverageinformationtoprioritizemodelinputs,underdifferent testing scenarios and resources.